Hidden treasures in stem cells of indeterminately growing bilaterian invertebrates - Vogt, Günter (Stem cell reviews and reports, 2012)
Indeterminate growth, the life-long growth without fixed limits, is typical of some evolutionarily very successful aquatic invertebrate groups such as the decapod crustaceans, bivalve molluscs and echinoderms. These animals enlarge their organs also in the adult life period and can regenerate lost appendages and organs, which is in sharp contrast to mammals and most insects. Interestingly, decapods, bivalves and echinoderms develop only rarely neoplastic and age-related diseases, although some species reach ages exceeding 100 years. Their stem cell systems must have co-evolved with these successful life histories suggesting possession of unknown and beneficial features that might open up new vistas in stem cell biology. Research of the last decade has identified several adult stem cell systems in these groups and also some mature cell types that are capable to dedifferentiate into multipotent progenitor cells. Investigation of stem and progenitor cells in indeterminately growing bilaterian invertebrates is assumed beneficial for basic stem cell biology, aquaculture, biotechnology and perhaps medicine. The biggest treasure that could be recovered in these animal taxa concerns maintenance of stem cell niches and fidelity of stem cell division for decades without undesirable side effects such as tumour formation. Uncovering of the underlying molecular and regulatory mechanisms might evoke new ideas for the development of anti-ageing and anti-cancer interventions in humans.